Development of skill certification system for bakers and cake decorators of a bakery manufacturing institution - Despabiladeras, Joan P. (University of the Philippines Diliman, 2014)
Within one year after the venture, the number of stores the manufacturing side of Company X is supporting increased from one to twelve. To support this, additional manpower is needed to complement the expansion project of the company. However, the quality of training of employees being deployed is compromised due to the insufficient time allotted for the activity. In addition, the operations of Company X are highly manual, employee skill dependent. In order to answer the challenge of maintaining product quality and consistency despite the large gap between the company strategic plans and the actual status of the employees' capability, a skill certification system is necessary. It is designed to contribute towards the continuous improvement of workers, recognizing and certifying the skills they possess and identifying those they need so as to enable them to become more productive and efficient, compete in the labor market, and bring them closer to the real needs of a productive bakery manufacturing. With new technologies and the shift to knowledge-based and globalized economies, it is beginning to be generally accepted that the contemporary workplace is characterized by (rather than merely subject to) continuous change.